Determining stakeholders' perceptions regarding the impacts of world heritage sites: A case study in Vredefort, Free State - Ngidi, Khanyisile Mbali Nicolet (Vaal University of Technology, 2022)
Tourism is the sum of phenomena and activities that arise from persons travelling to and staying in locations outside their usual place of residence for not more than one consecutive year. Tourism has impacts, which strongly affect an environment and society; hence, stakeholder’s perceptions on tourism impacts are important. The tourism industry’s impacts are usually classified into three categories, namely economic, environmental and socio-cultural, which are known as the triple-bottom line concept. The main aim of this study was to determine the stakeholder’s perceptions regarding the tourism impacts of the Vredefort Dome World Heritage Site (WHS) in the Free State province, South Africa. This study was quantitative in nature and followed descriptive research design, specifically a single-cross sectional study. A non-probability purposive sampling technique for the collection of data from government officials and the tourism businesses owners was used, while convenience sampling technique for the tourists and the local communities was also followed. Based on the results, the local communities’ respondents indicated minimal economic benefits from the WHS, while the tourists, tourism businesses owners and government officials slightly agreed to the presence of economic support and benefits. Based on the environmental impacts both the local communities and tourism business owners strongly agreed with the poor planning and management of the WHS. In terms of the socio-cultural findings, the local communities expressed their despondency towards the positive socio-cultural impact, while the tourist and business owners had neutral perceptions towards the socio-cultural benefits. The results show a strong relationship between stakeholder’s perceptions and the degree of awareness and participation/involvement of stakeholders in relation to tourism impacts. The study concludes that the local communities do not benefit economically, environmentally and socio-culturally from the Vredefort Dome WHS. The study also concludes that there is a relationship between awareness, participation/involvement and the perceptions created regarding tourism impacts. It is recommended that educational training and awareness should be adopted by the local municipality to change the local communities’ perceptions regarding tourism.
M. Tech. (Department of Tourism and Hospitality Management, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Stakeholders; Perceptions; Tourism; Impacts; World Heritage Site; Dissertations, Academic -- South Africa.; Tourism -- South Africa.; Heritage tourism.; Economic development -- South Africa.